Heidegger's Poetic Projection of Being - Geertsema, Marius Johan (Springer International Publishing, 2018)
This book investigates the relationship between poetry and ontology in the works of Martin Heidegger. It explains the way in which Heidegger's dialogue with poetry forms an essential step on the path of overcoming metaphysics and thinking the openness of presence. Heidegger's engagement with poetry is an important moment in the development of his philosophy-or rather thinking of Being. Being speaks itself poetically in his view. Rather than a logician or a thinker, Being is the first poet.